Development of Pastoral Economy in the 19th Century Serbian Village - Samardžić (Serbia), Momir; Bešlin (Serbia), Milivoj (Bulletin of the Institute of Ethnography SASA, 2018)
The basic thesis we are trying to prove in this paper is that the development and transformation of objects used for livestock breeding in Serbia in the 19th century represents a paradigmatic example of the dynamics of the economic development of the country. We believe that the gradual transition from animal husbandry as the dominant economic activity to land cultivation was accompanied by changes that conditioned the appearance, development and transformation of facilities for livestock breeding, gradually transforming them from temporary to permanent buildings, thus influencing the transformation of material culture. Key words: rural economy, animal husbandry, animal breeding facilities, Serbia, 19th century